Statistics on clouds and their relation to thermodynamic conditions at Ny-Alesund using ground-based sensor synergy - Nomokonova, Tatiana; Ebell, Kerstin; Loehnert, Ulrich; Maturilli, Marion; Ritter, Christoph; O'Connor, Ewan (COPERNICUS GESELLSCHAFT MBH, 2019)
The French-German Arctic research base AWIPEV (the Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research - AWI - and the French Polar Institute Paul Emile Victor - PEV) at Ny-Alesund, Svalbard, is a unique station for monitoring cloud-related processes in the Arctic. For the first time, data from a set of ground-based instruments at the AWIPEV observatory are analyzed to characterize the vertical structure of clouds. For this study, a 14-month dataset from Cloudnet combining observations from a ceilometer, a 94 GHz cloud radar, and a microwave radiometer is used. A total cloud occurrence of similar to 81 %, with 44.8% multilayer and 36% single-layer clouds, was found. Among single-layer clouds the occurrence of liquid, ice, and mixed-phase clouds was 6.4 %, 9 %, and 20.6 %, respectively. It was found that more than 90% of single-layer liquid and mixed-phase clouds have liquid water path (LWP) values lower than 100 and 200 g m(-2), respectively. Mean values of ice water path (IWP) for ice and mixed-phase clouds were found to be 273 and 164 g m(-2), respectively. The different types of single-layer clouds are also related to in-cloud temperature and the relative humidity under which they occur. Statistics based on observations are compared to ICOsa-hedral Non-hydrostatic (ICON) model output. Distinct differences in liquid-phase occurrence in observations and the model at different environmental temperatures lead to higher occurrence of pure ice clouds. A lower occurrence of mixed-phase clouds in the model at temperatures between -20 and -5 degrees C becomes evident. The analyzed dataset is useful for satellite validation and model evaluation.